A Longitudinal Study of Motor, Oculomotor and Cognitive Function in Progressive Supranuclear Palsy - Ghosh, Boyd C. P. (Public Library of Science, 2013)
OBJECTIVE: We studied the annual change in measures of motor, oculomotor and cognitive function in progressive supranuclear palsy. This had twin objectives, to assess the potential for clinical parameters to monitor disease progression in clinical trials and to illuminate the progression of pathophysiology. METHODS: Twenty three patients with progressive supranuclear palsy (Richardson’s syndrome) were compared to 22 matched controls at baseline and 16 of these patients compared at baseline and one year using: the progressive supranuclear palsy rating scale; the unified Parkinson’s disease rating scale; the revised Addenbrooke’s cognitive examination; the frontal assessment battery; the cubes section of the visual object and space perception battery; the Hayling and Brixton executive tests; and saccadic latencies. RESULTS: Patients were significantly impaired in all domains at baseline. However, cognitive performance was maintained over a year on the majority of tests. The unified Parkinson’s disease rating scale, saccadic latency and progressive supranuclear palsy rating scale deteriorated over a year, with the latter showing the largest change. Power estimates indicate that using the progressive supranuclear palsy rating scale as an outcome measure in a clinical trial would require 45 patients per arm, to identify a 50% reduction in rate of decline with 80% power. CONCLUSIONS: Motor, oculomotor and cognitive domains deteriorate at different rates in progressive supranuclear palsy. This may be due to differential degeneration of their respective cortical-subcortical circuits, and has major implications for the selection of outcome measures in clinical trials due to wide variation in sensitivity to annual rates of decline.